(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Lymphatic edema related to cancer is often caused by the removal of lymph nodes during surgery or radiation therapy. After treatment, patients are advised on "Rehabilitation exercises after breast cancer surgery" to raise awareness and prevent lymphatic edema in the same-side arm post-surgery. We conducted a study to describe the awareness and current practices of rehabilitation exercises after breast surgery. Objective: To describe awareness and the current situation of rehabilitation exercise practices, along with some factors influencing the awareness of rehabilitation exercises after breast surgery at the Hanoi Oncology Hospital in 2024 Methodology: A cross-sectional descriptive study conducted from April 2024 to August 2024 involving 142 breast cancer patients who have undergone surgery and are currently treated at the On-Demand Daycare Medical Oncology Department at Hanoi Oncology Hospital. Results: Patient awareness: Most patients recognize the signs of lymphedema, specifically swelling in the arm or hand (92.25%). The average score for awareness of the benefits of rehabilitation exercises in preventing lymphedema complications is high (4.19 points). The primary perceived barrier to exercising is the concern that rehabilitation exercises may cause additional fatigue, with an average score of 2.27 points. The most significant source of information regarding rehabilitation exercises comes from medical staff, with an average score of 4.30 points. Current status of patient practice: Most patients (83.8%) report no pain when practicing rehabilitation exercises. Patients’ occupations significantly affect their awareness of benefits, barriers, and information sources related to rehabilitation exercises, with a statistically significant difference (p < 0.05). Conclusion: Most patients are aware of the signs of lymphedema. Engaging in rehabilitation exercises can help prevent lymphedema complications without causing pain. Patients’ occupations influence their awareness and perceptions regarding exercise, highlighting the need for medical staff to provide tailored advice to help breast cancer patients mitigate and manage lymphedema complications after surgery.